The Feasibility Perception of Sports Applications to Maintain the Physical Conditions of Hockey Players During the Covid-19 Pandemic - Ardiyanto, Ahmad Rokhim; Suraya, Fatona (Sports Medicine Curiosity Journal, 2022)
The covid-19 pandemic has made a new adaptation for athletes. The purpose of this study is to analyze the use of 7 minutes workout and adidas running for fitness training of hockey athletes in Central Java during the covid 19 pandemic. Using survey methods with data retrieval techniques using questionnaires. The variables used are independent variables and variables tied to a sample of 20 athletes (10 male athletes and 10 female athletes). Data analysis techniques using descriptive statistics. The results showed that the free variable category is very good as many as 12 athletes (60%), as many as 7 athlete good category (35%), as many as 1 athlete bad category (50%), as many as 0 athletes very bad category (0%). While the variable is tied to very good categories as many as 10 athletes (50%), good categories as many as 9 athletes (45%), bad categories as many as 0 athletes (0%), very bad categories as many as 1 athlete (5.0%). The results showed that the physical impact of 7 minutes workout and adidas running on hockey athletes Central Java is very good. The conclusion of this study in the category of very good on both variables.